Diabelia, a new genus of tribe Linnaeeae subtribe Linnaeinae (Caprifoliaceae) - Landrein, Sven (Phytotaxa, 2013)
Recent molecular studies (to be published in a separate paper), have shown that the tribe Linnaeeae subtribe Linnaeinae (Caprifoliaceae s.l.) is composed of six monophyletic clades. These correspond to the genera Dipelta, Kolkwitzia, Linnaea and Vesalea, but Abelia appears polyphyletic. To resolve Abelia as monophyletic, and in order to keep most names currently in use within the horticultural and botanical community, the new genus Diabelia is proposed here to include the three species previously placed in Abelia ser. Serratae. Diabelia mainly differs from Abelia by its inflorescence of paired flowers appearing at the end of short shoots. A key to the genera is also presented. Additionally a new combination in Vesalea is validated here.